Інтертекстуальність як вияв поетики модернізму в доробку Ірини Жиленко - Сардарян, К. (Слово і Час, 2018)
У статті розглянуто особливості інтертекстуальної взаємодії текстів Ірини Жиленко з доробком класиків української (Т. Шевченко, Леся Українка, Г. Сковорода та ін.) і світової літератури (Дж. Джойс, Ван Вей, Рільке, Б. Брехт та ін.), а також фольклорними творами. Відлуння образів, стилів, мотивів, залучення цитат, форма сюжетних запозичень пояснюється особливостями поетичного самовираження мисткині, що продиктовано вподобаннями Ірини Жиленко, обізнаністю на світовій та вітчизняній літературах, фольклорі. Основні форми “чужого” слова в її творчості – цитати, а найчастіше – ремінісценції й алюзії із творів попередників, які при введенні в текст відсилають до відомого зразка, насичують твір додатковим смислом, демонструють шляхи наслідування ідеї, спадкоємності в засобах творення художньої моделі світу. Подальші дослідження покликані з'ясувати особливості інтертекстуальних паралелей у доробку Ірини Жиленко, їх ідентифікацію та інтерпретацію. The paper deals with the nature of intertextual relations of the texts by Iryna Zhylenko with the works by Ukrainian classical authors (T. Shevchenko, Lesia Ukrayinka, H. Skovoroda, etc.), the world literature (J. Joyce, Wang Wei, R. M. Rilke, B. Brecht, etc.), and also folklore works. The echo of images, styles, motives, the usage of quotations, and the forms of borrowing some plot details have been explained by the peculiarities of the poetic self-expression of the writer, dictated by her awareness of the world and national literature and folklore. The quotation is a frequent form of the writer’s borrowings, while the most often are reminiscences and allusions that refer to the known samples from the works of her predecessors, saturating the text with additional meanings and demonstrating continuity in the ways of creating the model of the artistic world. The further research intends to clarify the peculiarities of intertextual parallels in I. Zhylenko’s texts and interpret them. Zhylenko consciously used the intertext in her works, bringing a potent spirit of her personal ‘ego’ into the works. The mentioned aspects helped the writer in creating her individual style. The author’s peculiar lyricism, the features of existentialism, the realism of depicted reality, the usage of folklore elements and intertextuality as a specific element of Zhylenko’s discourse constitute an individual creative manner of the multifaceted works by the poet. Zhylenko’s individual style was worked out on the basis of a personal worldview and philosophical foundations of the 1960s. The author of the research states that the usage of the elements of intertextuality in the works by the writer speaks of interrelation of the tradition and innovations. В статье рассмотрен характер интертекстуального взаимодействия текстов Ирины Жиленко с произведениями классиков украинской и мировой литературы. Эхо образов, стилей, мотивов, использование цитат, форм сюжетных заимствований объясняются особенностями поэтического самовыражения писательницы, которые продиктованы предпочтениями И. Жиленко, глубокими знаниями мировой и отечественной литературы, фольклора. Основные формы “чужого” слова в ее творчестве – цитаты, а чаще всего – реминисценции и аллюзии из произведений предшественников, которые отсылают к известному образцу, насыщают текст дополнительным смыслом, демонстрируют идеи преемственности в способах создания модели художественного мира. Дальнейшие исследования предполагают рассмотрение особенностей интертекстуальных параллелей в текстах Жиленко, их идентификацию и интерпретацию.